Does Land Fragmentation Increase the Cost of Cultivation? Evidence from India - Deininger, Klaus; Monchuk, Daniel; Nagarajan, Hari K.; Singh, Sudhir K. (World Bank Group, Washington, DC, 2014)
Although a large literature discusses the productivity effects of land fragmentation, measurement and potential endogeneity issues are often overlooked. This paper uses several measures of fragmentation and controls for endogeneity and crop choice by looking at inherited paddy and wheat plots to show that these issues matter empirically. While crop choice can mitigate effects, fragmentation as measured by the Simpson index increases production cost and fosters substitution of labor for machinery, especially for small and medium farmers. Greater distances between fragments have a smaller effect. Creating opportunities for market-based consolidation could be one step to limit fragmentation-induced cost increases.